If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 10 = -5 Reorder the terms: 10 + 5p = -5 Solving 10 + 5p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5p = -5 + -10 Combine like terms: 10 + -10 = 0 0 + 5p = -5 + -10 5p = -5 + -10 Combine like terms: -5 + -10 = -15 5p = -15 Divide each side by '5'. p = -3 Simplifying p = -3
| 1/45+1/55=40x | | 14s-8s+3= | | 12+7=13x-8 | | M/6+11 | | 2.8x-09=5.2x-3.3 | | 3x-5-2.5x=8+.5x | | -x^2+100x-6400=0 | | 7(x-2)-7(4-x)= | | x(6x-11)=21 | | 28x+140=-28 | | 3(k+6)=-(k-3) | | x^2+1-2x/x^2-1 | | 2/3x-11=y+4 | | 5/8b+5=10 | | y=3/4x-6 | | 2u2/21 | | 2*22/7*1/3 | | 5/9y=32 | | (9x+8)(9x+8)=81x^2+64 | | 3(5-x)=-3x+12 | | 15x+108=33 | | f(x)=10+5x | | n(283.2)=158.13 | | -2a-3=3a+7 | | 7p+7=6(p+5) | | 15x+183=33 | | -4(m-8)=3m-3 | | 2(x+3)(x-5)=0 | | 3x+y=42 | | 1/6-11/12x+1=6 | | x^3+6x^2+3x=-18 | | 5x+3x+4x=189 |